A Cryptic Invasion in the Western Atlantic: Presence of the Fouling Barnacle Megabalanus zebra (Darwin, 1854) (Crustacea, Cirripedia) in the Caribbean Sea - Pitombo, Fabio Bettini; Gobin, Judith; Abreu, Nivia Maria Nunes; Jute, Alana (Zootaxa, 2017)
The barnacle Megabalanus zebra is largely known from ship hulls, with little information on its biology, ecology, and natural range. We identify M. zebra here from the southern Caribbean, based upon specimens collected as early as 2002. Challenges associated with identifying megabalinine species have delayed recognition of this species as distinct from other Caribbean Megabalanus. Sequenced material of M. zebra from Curaçao did not match M. zebra GenBank sequences that could be verified by descriptions or vouchered material. The presence of young M. zebra on vessels that have not left the Caribbean, as well as on pier pilings and resident buoys, indicate that this species is established in the tropical Western Atlantic Ocean, but the timing of its invasion remains unknown.